2021
DOI: 10.1111/dom.14399
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon‐like peptide‐1 receptor agonists improve biomarkers of inflammation and oxidative stress: A systematic review and meta‐analysis of randomised controlled trials

Abstract: Aim: To conduct a meta-analysis and systematic review to examine the effects of glucagon-like peptide-1 receptor agonists (GLP-1RAs) on clinical biomarkers of inflammation and oxidative stress in patients with type 2 diabetes.Methods: Medline, Embase and the Cochrane Library were searched for randomised controlled trials (RCTs) that examined changes with GLP-1RAs in a priori selected biomarkers of inflammation: C-reactive protein (CRP), adiponectin, tumour necrosis factor-alpha (TNFα), plasminogen activator in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 86 publications
3
42
2
1
Order By: Relevance
“…One pathophysiology of DMO consists of an inflammatory pathway, 38,45 and previous studies have indicated that diabetic patients with progression of renal dysfunction are associated with elevated serum interleukin (IL)‐6 and IL‐8 levels 46‐48 . Although both SGLT2 inhibitors and GLP‐1RAs could decrease systemic inflammation, 14,49 SGLT2 inhibitors may have more anti‐inflammatory effects in patients with renal dysfunction, based on our findings. Future investigations should confirm this observation and the hypothesis.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…One pathophysiology of DMO consists of an inflammatory pathway, 38,45 and previous studies have indicated that diabetic patients with progression of renal dysfunction are associated with elevated serum interleukin (IL)‐6 and IL‐8 levels 46‐48 . Although both SGLT2 inhibitors and GLP‐1RAs could decrease systemic inflammation, 14,49 SGLT2 inhibitors may have more anti‐inflammatory effects in patients with renal dysfunction, based on our findings. Future investigations should confirm this observation and the hypothesis.…”
Section: Discussionsupporting
confidence: 68%
“…One pathophysiology of DMO consists of an inflammatory pathway, 38,45 and previous studies have indicated that diabetic patients with progression of renal dysfunction are associated with elevated serum interleukin (IL)-6 and IL-8 levels. [46][47][48] Although both SGLT2 inhibitors and GLP-1RAs could decrease systemic inflammation, 14,49…”
Section: Discussionmentioning
confidence: 99%
“…Linagliptin, a DPP-4 inhibitor, has been shown to prevent these unfavorable effects, along with decreasing PAI-1 gene expression in endothelial cells [ 121 ]. Additionally, both vildagliptin and sitagliptin have been reported to decrease PAI-1 [ 122 , 123 ] levels in T2DM patients, in contrast to glucagon-like peptide-1 receptor agonists [ 124 ]. In a randomized trial, a 12-months long treatment with empagliflozin (10 mg/day, n = 31) has resulted in 25% decrease in PAI-1 concentration when compared with standard therapy [ 125 ].…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…This has been however attributed to the synergistic action on glucose metabolism, the weight loss and changes in leptin concentrations [ 125 ]. In polycystic ovary syndrome, exenatide was shown to decrease lysis time, without having any effect on clot density [ 124 ]. However, to date, there have been no reports on the effect of the new antidiabetic drugs on clot lysis time in patients with T2DM.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…In the gut, GLP-1 may control inflammation through binding to GLP-1 receptors on intestinal intraepithelial lymphocytes [11] . In favour of a clinically relevant role of GLP-1 in reducing systemic inflammation, a meta-analysis of randomised clinical trials concluded that GLP-1 receptor agonists reduce circulating levels of inflammatory biomarkers, including C-reactive protein and tumour necrosis factor (TNF)-α [12] . The clinical impact of GLP-1 in gut inflammation, however, remains uncertain.…”
Section: Introductionmentioning
confidence: 99%